An elastomeric patch derived from poly(glycerol sebacate) for delivery of embryonic stem cells to the heart - Chen, Qi-Zhi; Ishii, Hikaru; Thouas, George A.; Lyon, Alexander R.; Wright, Jamie S.; Blaker, Jonny J.; Chrzanowski, Wojciech; Boccaccini, Aldo R.; Ali, Nadire N.; Knowles, Jonathan C.; Harding, Sian E. (Biomaterials, 2010)
We hypothesize that a combinatorial approach of ventricle constraint and stem cell therapy would offer a greater benefit for the treatment of heart failure than either strategy alone. A heart patch would serve two therapeutic purposes: biomechanical support and cell delivery. In this study, we describe a hybrid heart patch engineered from a synthetic elastomer, poly(glycerol sebacate) (PGS), supplemented with cardiomyocytes differentiated from human embryonic stem cells (hESCs). In line with two therapeutically relevant considerations, i.e. biocompatibility and cell delivery efficiency, the PGS was (a) pre-conditioned in culture medium for 6 days, and (b) prepared without gelatin coatings to facilitate detachment and delivery of cardiomyocytes following patch implantation. Following pre-conditioning under physiological conditions, the PGS patch material without gelatin coating was found to satisfactorily support cardiomyocyte viability and attachment, with active cell beating for periods of longer than 3 months until interrupted. Dynamic culture studies revealed that cells detached more efficiently from the uncoated surface of PGS than from gelatin-coated PGS. No significant differences were detected between the beating rates of human embryonic stem cell-derived cardiomyocytes on tissue culture plate and the pre-conditioned and gelatin-uncoated PGS. PGS patches sutured over the left ventricle of rats in vivo remained intact over a 2 week period without any deleterious effects on ventricular function. We conclude that PGS is a suitable biomaterial for stem cell-based regeneration strategies to restore cardiomyocyte function, and the hybrid heart patch engineered under optimal conditions would be a promising support device for the cardiac repair. © 2010 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.anelas
Keywords: Embryonic stem cell; Heart; In vitro; In vivo; Poly(glycerol sebacate)